International evidence on the efficacy of new-Keynesian models of inflation persistence - Oleg Korenok; Stanislav Radchenko; Norman R. Swanson (Rutgers University, Department of Economics, 2011)
We take an agnostic view of the Phillips curve debate, and carry out an empirical investigation of the relative and absolute efficacy of Calvo sticky price (SP), sticky information (SI), and sticky price with indexation models (SPI), with emphasis on their ability to mimic inflationary dynamics. We look at evidence for a group of 13 OECD countries, and consider three alternative measures of inflationary pressure, including the output gap, labor share, and unemployment. We find that the SPI model is preferable to the Calvo SP and the SI models because it captures the type of strong inflationary persistence that has in the past characterized the economies in our sample. However, two caveats to this conclusion are that improvement in performance is driven mostly by lagged inflation and that the SPI model overemphasizes inflationary persistence. There appears to be room for improvement in all models in order to induce them to better track inflation persistence.
Keywords: E12; E3; C32; 330; sticky price; sticky information; empirical distribution; model selection; New-Keynesian Phillips Curve; Preisrigidität; Modellierung; Schätztheorie; Theorie; OECD-Staaten